The Role of Local Government in Dealing with The Impact of Climate Change on Agriculture in Bandung Regency - Wulandari, Septi; Deliarnoor, Nandang Alamsah; Yuningsih, Neneng Yani (Dinasti Research, 2025)
The agricultural sector in Bandung Regency faces significant challenges due to climate change, such as drought and flooding, resulting in a shift in the planting season. Local governments have a critical role in mitigating these impacts through three main functions, namely allocation, distribution, and stabilization. But the implementation is considered not optimal. The purpose of research is to analyze the role of the Bandung Regency Government in handling the impact of climate change in the agricultural sector through the approach of the three roles of the opinion of Musgrave: (a) the role of resource allocation; (b) the role of distribution of assistance and programs; (c) The role of farmers' economic stabilization. The method in this study uses qualitative with data collection techniques through in-depth interviews, observations of participants in several districts in Bandung Regency, and the study of policy documentation, reports, and related articles. Then the data is analyzed interactively using the Miles & Huberman model (data reduction, data presentation, verification of conclusions). The results obtained show that the role of the Bandung Regency Government has not been optimal in handling the impact of climate change in the agricultural sector